Implementing a Program to Remove Mercury in Small-Scale Gold Mining in Lebak Regency - Nurul, Wafa Nurul Hidayah; Widyastuti, Yeni; Stiawati, Titi (Epistemik Press, 2024)
This study aims to determine and analyze the implementation of the mercury removal program in the field of small-scale gold mining in Lebak Regency. Using the implementation model according to George Edwards III in Leo Agustino (2014: 149) there are four variables that determine the success of policy implementation, namely, communication, resources, disposition, and bureaucratic structure. The research method uses descriptive qualitative. The results showed that the implementation of the mercury removal program in the field of small-scale gold mining in Lebak Regency was still not optimal. There are several obstacles, namely the lack of awareness of the small-scale gold mining community on the impact of mercury hazards on human health and the environment, limited program budgets due to deductions due to the Covid-19 pandemic, the absence of monitoring or monitoring from the Lebak Regency Environmental Agency after socialization activities are carried out, the lack of quantity of human resources of the Lebak Regency Environmental Service, especially those in charge of spaciousness, the lack of optimal transfer of livelihoods to small-scale gold mining communities by the Lebak Regency Government, weak law enforcement carried out by the Lebak Police in dealing with illegal gold mining in Lebak Regency.